Reducing the risk of nosocomial Hepatitis B virus infections among healthcare workers in Nigeria: a need for policy directive on pre-employment screening and vaccination - Ogundele, Olorunfemi Akinbode (Pan Afr Med J, 2018)
Healthcare workers (HCWs) are at increased risk of contracting Hepatitis B virus (HBV) infection and other vaccine-preventable diseases, especially if they are not protected by immunity derived from previous infection or vaccination. Sub-Sahara Africa countries including Nigeria is reported to have the highest rate of HBV. Vaccination of HCWs is essential in protecting them from acute and chronic sequelae of HBV or any other form of vaccine-preventable diseases; however, HCWs vaccination remains a challenge for many developing countries including Nigeria due to lack of policy directive on pre-employment screening and vaccination. Poor political will and inadequate funding of healthcare in the country also impacts negatively on the implementation of effective pre-employment screening and vaccination programmes needed to protect HCWs. The aim of this opinion paper is to promote policy direction on pre-employment screening and vaccination in other to protect HCWs from nosocomial HBV infection. The most appropriate time perhaps for promoting the importance of employee immunisation is during pre-employment screening. The policy options are either for employers to allocate financial resources towards HCWs pre-employment screening and vaccination or alternatively initiate a programme where new HCWs provide evidence of protection against HBV or other vaccine-preventable diseases specified in the policy directive. Protecting HCWs form nosocomial HBV infection requires well-articulated policy directive, proper implementation, supported by adequate funding and good political will on the part of employers and government.